Enhanced Thermo‐Mechanical Stiffness, Thermal Stability, and Fire Retardant Performance of Surface‐Modified 2D MoS2 Nanosheet‐Reinforced Polyurethane Composites. Issue 1 (22nd November 2018) - Malkappa, Kuruma; Ray, Suprakas Sinha; Kumar, Neeraj
Abstract: This article reports new‐generation 2D‐MoS2 nanosheet‐containing polyurethane (PU) composite materials with improved thermo‐mechanical stiffness, thermal stability, and fire retardation properties. The surface of 2D‐MoS2 nanosheets is modified with melamine (M‐MoS2 ), and then PU composites with varying M‐MoS2 loadings are synthesized using an in situ polymerization method. During polymerization, 3‐amino‐propyl‐trimethoxy silane is introduced to create silicate functionality on the PU chains, which further improves the compatibility between PU and M‐MoS2 . Microscopy studies confirm the distribution of highly intercalated and agglomerated M‐MoS2 nanosheets in the PU matrix. The PU composite containing 5 wt% M‐MoS2 shows a 65% higher storage modulus (at 30 °C) than that of pure PU. The thermal stability of pure PU is significantly improved (62 °C) after composite formation. Thermogravimetric analysis in combination with FTIR spectroscopy shows that the PU/M‐MoS2 composites release less toxic gases during thermal degradation compared to pure PU. Moreover, the composite containing 5 wt% M‐MoS2 shows improved fire retardation properties, with 45% and 67.5% decrease in the peak heat and total heat release rates, respectively, as compared with those of pure PU. In summary, 2D‐MoS2 is shown to have potential as an advanced nano‐filler to obtain stiffer PU composite with improved fire retardant property for structural application. Abstract : This work reports the synthesis of melamine‐modified MoS2 nanosheets for use in development of flame‐retarding polyurethane composites with improved thermo‐mechanical stiffness and thermal stability. The image reports that the MoS2 nanosheets are randomly aligned in the polymer matrix by formation of strong interfacial hydrogen bonds with polymer chains, which is important to improve the property of resulting composites.